Unveiling external debt dynamics: Interdependencies of macroeconomic variables in ASEAN-7 - Sukanto, Sukanto; Azwardi, Azwardi; Mukhlis, Mukhlis; Atiyatna, Dirta Pratama; Hamira, Hamira (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study explores the interplay between external debt, infrastructure investment, epidemic response funding, net exports, and the consumer price index (CPI) in seven ASEAN countries—Indonesia, Myanmar, Thailand, Cambodia, Laos, the Philippines, and Vietnam—during the period from 2000 to 2020. Data were derived from the World Bank, OECD, and IMF. This research uses the autoregressive distributed lag model (ARDL) panel data approach to estimate the short-term and long-term relationships among the variables. Short-term results reveal that infrastructure investment, epidemic response funding, net exports, and the CPI do not significantly impact external debt. However, in the long-term analysis, epidemic response funding, net exports, and the CPI positively affect external debt. These findings have significant implications for policymakers in developing countries, especially within the ASEAN region.